Bruchus rufimanus Boheman (Coleoptera: Bruchidae) في نمو وتطور خنفساء الباقلاء الكبير Match تأثير مثبط تصنيع الكايتين - شفيق معـن عبد العزيز (Al-Nahrain Journal of Science, 2018)
Match, a benzoylphenylurea derivative, was tested topically at four doses (0.5, 1.0, 1.5 and 2.0 μg/insect) on adults of Bruchus rufimanus (Coleoptera: Bruchidae) (<24h-old), this was treated adults. First evaluated on fecundity,hatchability and viability of eggs laid by treated females and longevity of treated adults. The data showed that the growth regulator Match reduced the longevity and fecundity. In addition, treatments affected growth and development of egg-viability. In a second series of experiments, this IGR don’t induced significant reduction of the percentage-hatchability of eggs laid by F1 females which emergence from eggs laid by treated females, but its affect very significantly the viability rate of eggs laid by F1 females. Lengthened very significantly the total duration of the embryonic and post-embryonic development (larva and pupal stages) for eggs laid by treated females, when the concentration varied from 0.0 to 2.0 μg/ μl. The male adult descendant weight didn’t differ significantly between the control and the treatments with the doses of 0.5 and 1.0 μg/ µl. This weight decreased just significantly if the dose of the parents treatment was higher than 1.0 μg/ µl. When treated with the highest dose reduced significantly the adult longevity. On the other hand, this growth regulator didn’t affect the longevity of the first generation adults.